UANG PANGOLAT (TEBUSAN) DALAM PERKAWINAN MASYARAKAT TOBING JULU - Risalan Basri Harahap (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
There are habits that have been hereditary done in the implementation of marriage in society of Tobing Julu. That is giving ransom money (pangolat) by the male (groom) to the “anak namboru”  (anak namboru: a man who can marry a woman), which is requsted by  “anak namboru” at the time of leaving  woman from her home to her husband's home. The ordinance of this request is done by inhibiting the two brides outside the yard of  woman’s house by preparing a seat and a drink, then invite the two brides to sit together, at the time they will enjoy the drinks that have been provided. But if it is seen and observed in the implementation of customs about ransom money (Pangolat) committed by the community has largely deviated from the actual customary provisions. Based on those, if the habitual of giving  the ransom money (pangolat) in the implementation of marriage in Tobing Julu Kec Huristak Padang Lawas District has done suitable with actual custom, it will not contrary to Islamic law, then the law is allowed or ‘urf saheeh. On the contrary,  if the execution of the ransom money (pangolat) has deviated from the actual custom, so  the law will be included to the fasid ‘Urf or rejected